ChemInform Abstract: Industrially Viable Synthesis of 3‐[3‐(Trifluoromethyl)phenyl]propionaldehyde. A Key Intermediate to Cinacalcet. Issue 7 (18th February 2014) - Chavakula, Ramadas; Mutyala, Narayana Rao; Chennupati, Srinivas Rao
Abstract The improved synthesis of the title compound (II) includes the Corey‐Kim oxidation of alcohol (I) under normal conditions as key step.